Thematic Progression Patterns In The IELTS Task 2 Writing - Ebrahimi, Seyed Foad; Ebrahimi, Seyed Jamal (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--> This study investigated the thematic progression patterns in the Task 2, essays, of the writing section of the IELTS test. To this end, thirty Task 2 essays with a score of 8 and 8.5 were selected. Then, the data were analyzed based on the thematic progression model proposed by Eggins (2004). The findings suggested that the selections of the thematic progression patterns were directly imposed by the nature of the genre of essay writing. This means that the writers were required to select the thematic progression patterns in a way which help meeting the general goals and purposes of this genre. The finding could be used in the IELTS preparation writing classes to help the writers, especially EFL novice writers, to achieve satisfactory scores in the Task 2, essays, of the writing section of the IELTS test. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->